An industrial quality control study on Alaska Milk Corporation - Maputol, Arlene; Santos, Rowell; Tappa, Millette (Diliman, Quezon City College of Engineering, 2003)
This study deals with the production of liquid milk of Alaska Milk Corporation, specifically the products Evaporated Filled Milk (370 and 168 mL.) The group was able to document the present production and operations system of the company. After documentation, the group determined the issues regarding the different aspects of production planning, such as demand management, work-force management, aggregate planning, capacity and inventory management. With the different problems and issues usually encountered by the company, the group constructed a streamline diagnosis chart. After thoroughly analyzing the diagram, the three problem areas were identified. The three problem areas are: (1) inaccurate forecasting technique, (2) high cost of production plan, and (3) high reorder point for packaging materials for LCM. After identifying the three problem areas, the group generated alternative solutions and evaluated them by comparing the present system. With the proposed solution. Recommendations for each problem then followed. As for the first problem, which is inaccurate forecasting technique, the group recommends the use of Multiplicative Seasonal Model because the behavior of the demand exhibits a seasonal variation. Using the Multiplicative Seasonal Method, the group estimates a 97.51% decrease in inventory. For the second problem, which is high cost of production plan, the group made a new aggregate plan based on the new foretasted demand using the Multiplicative Seasonal Model. It was found that the forecasted demand can be met using production time of one shift., thereby decreasing the labor cost used in production. As for the third problem, the recommendation was the lowering of the reorder point for each type of liquid canned milk. Also, the reorder quantity was altered in relation to the new level of production. This decreased the holding cost of the packaging materials.
Submitted in partial fulfillment of the course requirements in IE 135 : Industrial Quality Control
Keywords: Alaska Milk Corporation; Milk industry; Quality Control